Research and Development Resource Allocation Under Rivalry - Scherer, F. M. (Quarterly Journal of Economics, 1967)
I. Returns and costs in the nonrivalrous case, 359. — II. The general rivalry problem, 363. — III. Specific duopoly models, 367. — IV. Solution concepts, 371. — V. Specific Cournot reaction patterns, 377. — VI. The N-firm problem, 389. — VII. Welfare implications, 392. — VIII. Conclusion, 394.